Analisis Sikap yang Diambil oleh Pemerintah Korea Selatan pada Masa Presiden Park Geun Hye Terkait dengan Isu Comfort - Lalitya, Galuh Kinnari; Wahyudi, Fendy Eko (Journal of International Relations, 2020)
Countries in East Asia have fluctuating relationships. Various issues cause conflict betweenthese countries and their allies such as the United States. One of the issue that remain becomea problem is historical issue related to comfort women. This problem involves South Koreaand Japan as the main actors. Often there are tensions between the two countries because ofthis issue. The comfort women issue has also caused several agreements to fail. South Koreanvictims, government, and activists continue to seek official recognition and requests from theJapanese government. Park Geun Hye, has actively criticized and pressured the JapaneseGovernment just as the previous presidents had done. However, Park changed his attitude byagreeing to the â€œfinal and irreversibleâ€ 2015 Agreement on the issue of comfort women. Thisraises pros and cons among both the government and the people of South Korea itself. Thepurpose of this study was to determine what influenced Park's changes in attitude and policy.To analyze the effect of the policies taken, this study uses an international systems approachand offensive realism theory.